2021
DOI: 10.52657/js.v7i1.1332
|View full text |Cite
|
Sign up to set email alerts
|

English Students’ Perception on Critical Thinking Pedagogical Techniques

Abstract: The purpose of the research was to discover students’ perceptions of critical thinking pedagogical techniques. The type of research was designed by using a survey that shared the link of online questionnaires to the participants. Based on the result of research, students agree if critical thinking skills should be taught during class and understood the pedagogical methods to develop a higher order of thinking skills. However, it needs more development in some techniques, and to see the implementation of this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…There are similar studies discussed the students' perceptions of thinking skills, such as research conducted by Febria (2021), she intends to discover students' perceptions of critical thinking pedagogical techniques in Universitas International Batam. The result showed that students agree with learning that integrates critical thinking skills and support teachers' efforts to put new methods or tactics into practice in the classroom.…”
Section: Introductionmentioning
confidence: 98%
“…There are similar studies discussed the students' perceptions of thinking skills, such as research conducted by Febria (2021), she intends to discover students' perceptions of critical thinking pedagogical techniques in Universitas International Batam. The result showed that students agree with learning that integrates critical thinking skills and support teachers' efforts to put new methods or tactics into practice in the classroom.…”
Section: Introductionmentioning
confidence: 98%